Learning 2-Dimensional and 3-Dimensional Geometry with Geogebra: Which Would Students Do Better? - Ismail, Zaleha; Rahman, Syairatul Nadiah Abd (International Journal on Emerging Mathematics Education, 2017)
The purpose of this study is to examine the geometric thinking of young children who worked with GeoGebra to learn two-dimensional (2-D) and three-dimensional (3-D) geometry. GeoGebra is an open sourced dynamic mathematics software which is applicable for learning mathematics from primary school to secondary school and to higher education. Thirty pupils studying in second grade (Year 2) at a school located in Pontian, a district in one of the Malaysian state participated in the study. They attended GeoGebra sessions to construct and analyze dynamics of two-dimensional and three-dimensional geometry after learning these topics in the conventional setting. Pretest and posttest on two-dimensional and three-dimensional spatial ability based on Van Hiele level of geometric thinking were administered to the pupils. The comparison between pretest and posttest results demonstrate significant enhancement in visualization and informal deduction for both 2-D and 3-D geometry. Moreover from the intervention, the students benefit most in analyzing 3-D and visualizing 2-D geometry. Interestingly, skills and knowledge acquired through activities using GeoGebra in student-centered learning environment could be successfully transferred to paper and pencil test.